Feasts : archaeological and ethnographic perspectives on food, politics, and power - Dietler, Michael; Hayden, Brian (University of Alabama Press, 2010)
From the ancient Near East to modern-day North America, communal consumption of food and drink punctuates the rhythms of human societies. Feasts serve many social purposes, establishing alliances for war and marriage, mobilizing labor, creating political power and economic advantages, and redistributing wealth. In this collection of fifteen essays, archaeologists and ethnographers explore the material record of food and its consumption as social practice. They examine the locations of roasting pits, hearths, and refuse deposits, or the presence of special decorative ceramics, and infer ways.